Artificial intelligence-enhanced assessment of fundamental motor skills: validity and reliability of the FUS test for jumping rope performance - Makaruk, Hubert; Porter, Jared M.; Webster, E. Kipling; Makaruk, Beata; Tomaszewski, Paweł; Nogal, Marta; Gawłowski, Daniel; Sobański, Łukasz; Molik, Bartosz; Sadowski, Jerzy (Frontiers in Artificial Intelligence, 2025)
IntroductionFundamental motor skills (FMS) are foundational for lifelong physical activity and talent development. However, their development is often overlooked in favor of sport-specific outcomes in physical education (PE). This study aimed to evaluate FMS proficiency among students enrolled in traditional and school-based sport PE programs and explore implications for early specialization and motor competence.MethodsWe assessed FMS proficiency in a large sample of Polish students aged 10–14 (N = 2,238) using the validated Fundamental Motor Skills in Sport (FUS) test. Participants were grouped based on enrollment in traditional PE or school-based sport PE programs. Proficiency was classified into four levels based on mastery across six motor tasks.ResultsThe majority of students in both groups failed to meet the basic FMS proficiency threshold. Specifically, 72% of boys and 77% of girls in sport PE programs were below elementary proficiency, compared to 90% of boys and 92% of girls in traditional PE. While sport PE students outperformed their peers, significant deficits remained. Gender differences showed boys had advantages in object control skills, while girls performed better in coordination-oriented tasks.DiscussionBoth traditional and sport PE programs fall short of supporting adequate FMS development, potentially due to overemphasis on early specialization and lack of instructional support for motor competence. These findings underscore the need for curricular reforms and targeted teacher training to prioritize broad motor skill development and promote long-term participation in physical activity.